A Report on Pathomorphological Study of Pyothorax in a Cat - A. Manasa; R. Anoopraj; M. Pradeep; P. Hamza; J.G. Ajith; R. Rajasekhar; Athira P. Nair (The Indian Veterinary Journal, 2024)
The life-threatening emergency of feline pyothorax is one that small animal veterinarians frequently deal with. An eight-month-old female Persian cat was presented with the history of dyspnoea, nasal discharge, vomiting, diarrhoea, severe emaciation and weight loss. Animal was under treatment for respiratory distress for six days and collapsed. At necropsy, fibrin deposits over the pleura and unilateral accumulation of creamy fluid in the thoracic cavity were observed. Histopathological examination of lung showed fibrinous pleuritis with marked inflammatory cell infiltration, prominent vascular changes and diffuse alveolar damage.